1976
DOI: 10.1142/s0192415x76000494
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Acupuncture Stimulation on Plasma Levels of LH, FSH, Progesterone and Estradiol in Normallly Ovulating Women

Abstract: This is the first attempt to elucidate the direct effect of acupuncture stimulation on plasma levels of LH, FSH, progesterone and estradiol in normally ovulating women. Four loci, which are known from experience to relate closely to female reproductive organs, were needled with electric stimulation and the responses to synthetic LH-RH with and without acupuncture stimulation were also analyzed in the same cases. Plasma hormone levels were measured by specific radioimmunoassy. All cases showed normal responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 0 publications
0
14
0
2
Order By: Relevance
“…AP-type stimuli influence reproductive organs and functions, including release of LH, FSH, P 4 and E 2 [33,34] . There are several studies on AP affecting the function of the CL [35,36] .…”
Section: Discussionmentioning
confidence: 99%
“…AP-type stimuli influence reproductive organs and functions, including release of LH, FSH, P 4 and E 2 [33,34] . There are several studies on AP affecting the function of the CL [35,36] .…”
Section: Discussionmentioning
confidence: 99%
“…11 The study by Aso et al revealed that acupuncture influences plasma levels of FSH, LH, endorphin, and substance P in women both with normal ovulation and also with anovulation. 12 The acupuncture point CV 4 is the intersecting point of the Kidney, Liver, and Spleen channels. Therefore, this point can potentiate the effects of other points on those channels.…”
Section: Discussionmentioning
confidence: 99%
“…β-EP is derived from its precursor protein pro-opiomelanocortin, which is present in abundant amounts in neuronal cells of the arcuate nucleus of the hypothalamus, pituitary, medulla, and in peripheral tissues including intestines and ovaries [40][41][42]. Pro-opiomelanocortin cleaves to form adrenocorticotropic hormone and β-lipoprotein.…”
Section: B-endorphinmentioning
confidence: 99%
“…It shows that acupuncture can increase the serum E2 content and decrease the serum FSH and LH levels in the patients. Acupuncture may improve the function of the HPOA, increase blood adrenogenous androgen level and facilitate its transformation into estrogen by aromatic enzyme in the brain, liver and fat tissues [40][41][42]. In comparison with HRT, the body's own functions may be regulated with the use of acupuncture, while HRT restores the body's hormone level by exogenous hormones.…”
Section: B-endorphinmentioning
confidence: 99%